2023
DOI: 10.3847/2041-8213/acc531
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Magnetic Field Fluctuations and Their Spectral Properties within the Heliosphere: Statistical Approach

Abstract: We present the first comprehensive statistical study of the evolution of compressive and noncompressive magnetic field fluctuations in the inner heliosphere. Based on Parker Solar Probe (PSP) and Solar Orbiter data at various distances from the Sun, we show the general trends and compare them with Wind observations near 1 au. The paper analyzes solar wind power spectra of magnetic field fluctuations in the inertial and kinetic ranges of frequencies. We find a systematic steepening of the spectrum in the inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In this paper a transition in the magnetic field spectral index has been shown from −5/3 far from the Sun to −3/2 close to the Sun, with the transition occurring at around 50 R e . This is in agreement with previous observations (Chen et al 2020;Shi et al 2021;Šafránková et al 2023;Sioulas et al 2023), although Lotz et al (2023), using data from the fifth orbit of PSP, found only a weak trend with distance, with the spectrum possibly steeper closer to the Sun. However, this work appears to use a considerably higher frequency range to determine the index than the other work referenced.…”
Section: Discussionsupporting
confidence: 93%
“…In this paper a transition in the magnetic field spectral index has been shown from −5/3 far from the Sun to −3/2 close to the Sun, with the transition occurring at around 50 R e . This is in agreement with previous observations (Chen et al 2020;Shi et al 2021;Šafránková et al 2023;Sioulas et al 2023), although Lotz et al (2023), using data from the fifth orbit of PSP, found only a weak trend with distance, with the spectrum possibly steeper closer to the Sun. However, this work appears to use a considerably higher frequency range to determine the index than the other work referenced.…”
Section: Discussionsupporting
confidence: 93%
“…The regime where kλ i = 1 and kρ i = 1 (k is the wavenumber of the magnetic field fluctuations in the plasma frame) is called the inertial range. The power spectrum of the magnetic field fluctuations in this range evolves with the distance from the Sun from an Iroshnikov-Kraichnan power law with the exponent of −3/2 toward the Kolmogorov-like exponent of −5/3 observed at 1 au (Chen et al 2020;Zhao et al 2022b;Šafránková et al 2023;and references therein).…”
Section: Introductionmentioning
confidence: 85%
“…A statistical study of the evolution of the solar wind will help us understand the origin of the solar wind and the physical mechanisms involved. Especially, considering the near-Sun solar wind may carry more coronal source characteristics, the accurate radial evolution of the near-Sun solar wind may be not consistent with the prediction of previous models at larger heliocentric distance (Halekas et al 2020;Abraham et al 2022;Mostafavi et al 2022;Šafránková et al 2023;Liu et al 2023). Therefore, in this Letter, we aim to present the radial evolution of solar wind parameters below 0.3 au by analyzing PSP observations from Encounters 1-15 statistically.…”
Section: Introductionmentioning
confidence: 97%